Typology and Feature Checking of Wh-Questions - Ma, Daoshan (Master Program in Linguistics, Diponegoro University, 2017)
From the perspective of the syntactic behavior of wh-questions, natural languages can be classified into four types: Null Spec Language, Single Filled Spec Language, Multiply Filled Spec Language and Non-Multiply Filled Spec Language. Data were collected according to the relevance to the present research from each representative of the four types of languages, namely, Chinese, English, Bulgarian and Czech. Some of the data in the thesis were taken from the previous literature. Others were from self-introspection. The collected data were analyzed from the point of typology and feature checking. Feature checking in wh-questions of these four types of languages seem to be operated quite differently. Pied-piping of the formal features of the wh-words or wh-phrases occur in English, Bulgarian and Czech but not in Chinese. However, feature movement in wh-questions of these four types of languages is universal. This finding proves Chomsky’s biological linguistic belief that language is mainly an optimal solution to conditions it must satisfy.